Developing Scientific Article Writing Materials Using a Hybrid Learning Approach: Insights from an Indonesian Language for Foreign Speakers (BIPA) Program - Ah. Rofiuddin; Didin Widyartono; Gatut Susanto; David Pickus (Graduate School of Universitas Negeri Malang, 2022)
This study aims to produce learning materials for writing scientific articles for foreign students using the hybrid learning approach. This approach was chosen by utilizing the advantages of offline classes combined with online classes. This approach is in accordance with the characteristics of students as millennials. The development research method used consists of product design, product design, production, and product testing. The end result is learning materials to write scientific articles that are packaged in the form of modules, starting from the debriefing of concepts (f2f), planning of writing (f2f), writing a draft (ol), and editing the draft (f2f) writing process-genre based scientific articles with a hybrid learning approach for foreign students